ANALISIS STRATEGI MANAJEMEN ZAKAT PADA BAZNAS KABUPATEN BONDOWOSO DAN JEMBER - Hamim (Jurnal Ekonomi Syariah Darussalam, 2024)
Data from the Strategic Study Center of the Badan Amil Zakat Nasional (BAZNAS) Institutional Index Rating in East Java indicates that Bondowoso Regency has a score of 0.42 (fairly good) and Jember has a score of 0.45 (fairly good). In terms of ranking, Bondowoso and Jember are ranked 21st and 20th out of 23 regencies/cities, respectively. This presents a challenge for these two regencies, considering the Zakat index with institutional indicators (collection, management, distribution, and reporting) is very low and almost approaches the Poor Zakat index (0.21-0.40). This research employs a descriptive qualitative research method and data collection techniques in the form of observation, interviews, and documentation. The findings of this research are: 1) The management of zakat at BAZNAS has been effective and in accordance with Law Number 23 of 2011 & BAZNAS RI Regulation Number 1 of 2023. 2) The supporting and inhibiting factors in BAZNAS can be well collaborated, so that according to SWOT analysis, these two BAZNAS are in a strategy of supporting aggressive growth policies.